A Survey and experimental verification of Modular Multilevel Converters - Sreedhar Madichetty; Dasgupta Abhijit; Sivaji Jinka (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This article is devoted to the Multi-level converters review and specifically the form and function of modular multilevel converter (MMC) with their modulation, design considerations, balancing issues, control schemes, and applications. This article intends to make a detailed analysis of MMC with their controller related issues in comprehensive manner. It is an approach for MMC design and modulation schemes in easy manner. Furthermore, a five level MMC have been designed with optimal controller and verified by its experimental results and explored. In addition to that, this approach draws strategic conclusions on MMC towards making the system more robust in operation, less complex in design and control.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5914